Gains From Training in Phonological Awareness in Kindergarten Predict Reading Comprehension in Grade 9 - Kjeldsen AC; Karna A; Niemi P; Olofsson A; Witting K (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
The effects of a kindergarten training program in phonological awareness with 209 Swedish-speaking children were followed up until the end of Grade 9. Initial levels of letter knowledge and phonological awareness were positively associated with the level of decoding skill in Grade 3 but not with its growth afterward. The intervention group performed significantly better in decoding in Grade 3, and the difference was maintained until Grade 6. The trained children also scored higher in Grade 9 reading comprehension. Although the results give empirical support for a connection between early phonological awareness training, later word decoding development, and still later reading comprehension, the theoretical explanation for the link between especially word decoding and reading comprehension is far from clear.